1994
DOI: 10.1093/oxfordjournals.jhered.a111453
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Genetic Variation in Southern African Black Rhinoceros (Diceros bicomis)

Abstract: Thirty protein-coding loci of southern African black rhinoceros (Diceros bicornis) from four isolated populations were studied using starch gel electrophoresis and polyacrylamide gel electrophoresis. Gene diversity estimates varied between 0.036 and 0.058, with the Zambezi Valley population having the largest amount of protein variation. These levels are higher than those in other studies of genetic variation in black rhinoceros and are similar to the amount of genetic variation observed for outbred natural po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…Our findings of no appreciable genetic signatures of a bottleneck in D. b. bicornis are consistent with the expectation that changes in genetic diversity depends on a bottleneck's length and severity, as well as the mutation rate of the loci (Piry et al 1999). The long generation time (*12 years), length of the reproductive lifespan, admixture from translocation, and rapid population recovery may have limited the effect of a recent bottleneck on D. b. bicornis (Swart et al 1994). A lengthy lifespan and a large variance in effective population size, prior to severe population declines, has been offered as the explanation for high genetic variation in a broad set of organisms that experienced recent bottlenecks, from the greater one-horned rhinoceros (Rhinoceros unicornis; Dinerstein and McCracken 1990) to white-tailed eagles (Haliaeetus albicilla; Hailer et al 2006).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings of no appreciable genetic signatures of a bottleneck in D. b. bicornis are consistent with the expectation that changes in genetic diversity depends on a bottleneck's length and severity, as well as the mutation rate of the loci (Piry et al 1999). The long generation time (*12 years), length of the reproductive lifespan, admixture from translocation, and rapid population recovery may have limited the effect of a recent bottleneck on D. b. bicornis (Swart et al 1994). A lengthy lifespan and a large variance in effective population size, prior to severe population declines, has been offered as the explanation for high genetic variation in a broad set of organisms that experienced recent bottlenecks, from the greater one-horned rhinoceros (Rhinoceros unicornis; Dinerstein and McCracken 1990) to white-tailed eagles (Haliaeetus albicilla; Hailer et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…A lengthy lifespan and a large variance in effective population size, prior to severe population declines, has been offered as the explanation for high genetic variation in a broad set of organisms that experienced recent bottlenecks, from the greater one-horned rhinoceros (Rhinoceros unicornis; Dinerstein and McCracken 1990) to white-tailed eagles (Haliaeetus albicilla; Hailer et al 2006). In addition, protein electrophoretic assays of D. bicornis minor found levels of genetic diversity, after the severe population bottleneck in southern Africa, to be similar to levels in a larger population of D. b. minor that was not known to have undergone a bottleneck (Swart et al 1994;Swart and Ferguson 1997). Ancestral population size variation among the subspecies of black rhinoceros, which is not accounted for in the bottleneck analyses used here and in Harley et al (2005), may also result in the differences in current genetic variation and the lack of genetic evidence for recent bottleneck effects in these taxa (Tajima 1989;Marth et al 2004).…”
Section: Discussionmentioning
confidence: 89%
“…One of their main conclusions was that the Zambezi population is particularly important because of its large genetic variation. Their results indicate that the Zambezi Valley (Zimbabwe) is potentially the only remaining population containing much of the genetic variation that existed before the turn of the century (Swart et al . 1994; Swart & Ferguson 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Swart et al (1994), using mtDNA, demonstrated the persistence of genetic diversity in small populations of black rhinoceros that had undergone demographic contraction; highlighting the need to conserve even small populations. Behavioural observations in Lewa Down Wildlife Conservancy indicated that black rhinoceros males are polygynous, with a high variance in reproductive success, suggesting a potential benefit of moving males among populations to reduce mate competition and increase male effective population size (Merz 1994).…”
Section: Introductionmentioning
confidence: 99%